A Probable Rickettsial Trigger for Hemophagocytic Lymphohistiocytosis: Murine Typhus - Shreya Kondle; Sharon A. Secola; Khoan Vu (Annals of Internal Medicine: Clinical Cases)
Hemophagocytic lymphohistiocytosis (HLH) is a serious hyperinflammatory condition with hyperactive cytotoxic T cells and macrophages that can be triggered by various infections, malignancies, and rheumatologic conditions. Herein, we present a rare case of secondary HLH due to probable murine typhus. A 65-year-old man presented with generalized weakness, anemia, thrombocytopenia, and elevated liver enzymes. Evaluation revealed extremely elevated ferritin and presence of hemophagocytosis on bone marrow aspirate. He was initially treated with dexamethasone and etoposide for suspected HLH, but additional evaluation confirmed typhus group positivity. With initiation of doxycycline, the patient's clinical condition rapidly improved.